2016
DOI: 10.1103/physreva.93.013611
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar bilayer with antiparallel polarization: A self-bound liquid

Abstract: Dipolar bilayers with antiparallel polarization, i.e. opposite polarization in the two layers, exhibit liquid-like rather than gas-like behavior. In particular, even without external pressure a self-bound liquid puddle of constant density will form. We investigate the symmetric case of two identical layers, corresponding to a two-component Bose system with equal partial densities. The zerotemperature equation of state E(ρ)/N , where ρ is the total density, has a minimum, with an equilibrium density that decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Then using the correlated basis function (CBF) method they obtained its dynamical properties. It has been also suggested that a bilayer system of dipolar bosons becomes a self-bound fluid when the polarization of dipoles in two layers is opposite [39]. More recently, the competition between single-dipole and dimer condensation in a bilayer of perpendicular dipolar bosons with parallel polarization, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Then using the correlated basis function (CBF) method they obtained its dynamical properties. It has been also suggested that a bilayer system of dipolar bosons becomes a self-bound fluid when the polarization of dipoles in two layers is opposite [39]. More recently, the competition between single-dipole and dimer condensation in a bilayer of perpendicular dipolar bosons with parallel polarization, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ground state can be obtained, for example, from quantum Monte Carlo simulations. This provides exact ground state properties of dipolar quantum gases [22][23][24][38][39][40][41] , but it would be computationally very demanding for the large number of layers that we study in this work. For the fairly low partial denstities ρ α that we consider here, it is sufficient to use approximate methods.…”
Section: Correlated Basis Function Theorymentioning
confidence: 99%
“…In a previous work, 24 we presented energetic and structural results for the liquid-like ground state of two 2D dipolar Bose gas layers (with anti-parallel polarization), using the multi-component generalization of the hypernetted chain Euler-Lagrange (HNC-EL) method. [25][26][27][28][29][30] In Ref.…”
Section: -23mentioning
confidence: 99%
See 2 more Smart Citations